Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. (22nd January 2016) - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al.
Graphical abstract: Highlights: In a murine model of asbestos exposure a relevant inflammatory and atypical hyperplastic reaction was induced. Inflamed lung tissue regions of mice exposed to crocidolite, 1 month after treatment, were analyzed at two different synchrotron facilities: a high and a low energy microscopy set-up. Where conventional histochemical staining procedures fail to reveal any significant calcium and iron deposition, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the macrophage ingested fibers. Asbestos fibers can induce iron and calcium ions sequestration early on following exposure. This process is concomitant with the appearance of inflammatory and hyperplastic reactions. Abstract: Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.